Islam and Democracy Law, Gender and the West - Barakat, Zeina M.; Münchow, Thies; Wüstenberg, Ralf K. (Reconciliation and Conflict Resolution (ReCo), 2022)
This volume breaks new ground by harnessing the views of seventeen distinguished scholars from a range of disciplines who are addressing key questions surrounding the tensions between fundamental ideas of international law, post-colonial and feminist thought on the one hand and Sharia law and protection of belief on the other.